The antigen processing-associated transporter gene polymorphism: Role on gene and protein expression in HPV-infected pre-cancerous cervical lesion - Medeiros, Fernanda Silva; Silva, Mauro César da; Silva, Neila Caroline Henrique da; Gomes, Thailany Thays; Gomes, Renan Garcia; Paiva, Larissa Albuquerque; dos Santos Gomes, Fabiana Oliveira; Peixoto, Christina Alves; Rygaard, Maria Carolina Valença; Welkovic, Stefan; Menezes, Maria Luiza Bezerra; Donadi, Eduardo Antônio; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Human papillomavirus (HPV) is the major pathogen for cervical lesions. The evasion mechanism of the immune response and persistence of HPV infection can be influenced by polymorphisms (SNPs) in genes associated with transporter associated with antigen processing (TAP), which may change the peptide binding affinity or the TAP expression impacting the efficiency of peptide transport in the secretory pathway, and the presentation of peptides to cytotoxic T lymphocytes. This study aimed to evaluate the role of the TAP1 and TAP2 polymorphisms, TAP1, and TAP2 genes expressions, and protein levels in cervical cells presenting different degrees of pre-cancerous lesions in 296 immunocompetent women infected or not by HPV. TAP SNPs were genotyped by Sanger sequencing, and gene expression by real-time PCR. Aneuploidy was determined by DNA index using flow cytometry. TAP-1 and TAP-2 tissue expressions were evaluated by immunohistochemistry. The Asp697Gly SNP of TAP1 presented a risk for cellular aneuploidy (P=0.0244). HPV+ women had higher TAP-2 mRNA (P=0.0212) and protein (P<0.0001) levels. The TAP2D and TAP2E haplotypes were associated with the risk for aneuploidy and pre-cancerous lesions. In conclusion, nucleotide variability at the peptide binding region of peptide transporter genes, particularly of the TAP2 gene, may influence the HPV-peptide transportation from the cytosol to the endoplasmic reticulum, increasing the susceptibility to the development of high-grade cervical lesions.